2017
DOI: 10.1111/and.12923
|View full text |Cite
|
Sign up to set email alerts
|

Expression of paraoxonase types 1, 2 and 3 in reproductive tissues and activity of paraoxonase type 1 in the serum and seminal plasma of bulls

Abstract: The paraoxonases types 1, 2 and 3 (PON1, PON2 and PON3, respectively) are enzymes that degrade lipid peroxides, preventing oxidative damages relevant for male reproductive function. This study determined the expression of those three paraoxonases in reproductive tissues of bulls and evaluated correlations among the activity of PON1 in the serum and seminal plasma with breeding soundness parameters in bulls. The expression of PON1, PON2 and PON3 was characterised by RT-PCR in samples of testicular parenchyma, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Our findings indicate that, among all tested sources, the PON1 activity in the sperm-rich portion of ejaculates may be a candidate biomarker for boar fertility, as indicated elsewhere (Barranco et al, 2015b;Ferreira et al, 2018), since ejaculates with increased PON1 activity in the sperm-rich portion would be more likely to have increased sperm concentration and greater frequency of spermatozoa with DNA integrity. In the present study, the two boars presenting the greatest PON1 activity in the sperm-rich portion of their ejaculates (Boars 2 and 3) were also those presenting the greatest sperm concentration, reflecting the fact that the sperm-rich portion presents greater sperm concentration (Peña et al, 2004).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our findings indicate that, among all tested sources, the PON1 activity in the sperm-rich portion of ejaculates may be a candidate biomarker for boar fertility, as indicated elsewhere (Barranco et al, 2015b;Ferreira et al, 2018), since ejaculates with increased PON1 activity in the sperm-rich portion would be more likely to have increased sperm concentration and greater frequency of spermatozoa with DNA integrity. In the present study, the two boars presenting the greatest PON1 activity in the sperm-rich portion of their ejaculates (Boars 2 and 3) were also those presenting the greatest sperm concentration, reflecting the fact that the sperm-rich portion presents greater sperm concentration (Peña et al, 2004).…”
Section: Discussionsupporting
confidence: 56%
“…Reduced PON1 activity was observed in the seminal plasma of men presenting teratozoospermia, azoospermia, subfertility and infertility (Verit et al, 2009;Gulum et al, 2017;Ozer et al, 2019), whereas increased PON1 activity was positively associated with sperm concentration (Ozer et al, 2019). In bulls, PON1 activity in the seminal plasma presented positive correlations with a subjective indicator of sperm concentration and with several parameters of sperm quality (Ferreira et al, 2018). In boars, greater PON1 activity in the seminal plasma was positively correlated with sperm concentration (Barranco et al, 2015b) and associated with increased motility, reduced production of ROS (Barranco et al, 2015a), improved cryotolerance (Li et al, 2018) and increased farrowing rates after AI (Barranco et al, 2015b).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, several imprinted genes were related to behavioral functions. The second group, which involved the imprinted gene Ube3a , has been reported to regulate sleep homeostasis 57 ; the fifth group, which involved the imprinted gene Ntm , has been reported to be involved in motor function 58 ; the thirteenth group involved four imprinted genes ( Gpr1 , Nnat , Htra3 , and Pon2) , which regulate reproduction 59–62 ; and the fourteenth group involved four imprinted genes ( Dcd , 63 Ppo1r9a , 64 Slc22a2 , 65 and Pde4d 66 ) reported to mediate learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…BSP5 presented a positive correlation with abnormal sperm in fresh semen, but negative with abnormal sperm in frozen-thawed semen (Menezes et al 2017). Spermadhesin 1 and paraoxonase (PON1) were negatively correlated with sperm vigor, whereas CLU exhibited a positive association with this parameter (Menezes et al 2017;Ferreira et al 2017). BSP5 and CLU had positive correlations with the viability of bovine sperm (Menezes et al 2017), and seminal gamma glutamyl transferase (GGT) activity showed positive associations with in vitro embryo development (Pero et al 2017).…”
Section: Tablementioning
confidence: 99%